Embodied Energy Consumption in the Residential Sector: A Case Study of Affordable Housing - Anderson N; Wedawatta G; Rathnayake I; Domingo N; Azizi Z (MDPI (Basel, Switzerland), 2022)
Embodied energy has a significant effect on the total environmental impact of a project. However, emphasis is often placed primarily on operational energy, resulting in a knowledge gap about the current state of embodied energy use in affordable housing. To address this, the study investigates the level of embodied energy consumption in affordable housing, as well as the drivers, barriers, and techniques to reduce embodied energy. Based on a single embedded case study covering the period from cradle to end of construction, data were collected using embodied energy calculations of three affordable housing units in the project, semi-structured interviews with five design team members, and a cross-examination of findings with contract documents. The results were analysed using sensitivity analysis and thematic analysis. The findings revealed that all three house units fulfilled the baseline embodied carbon target of 800 kg CO2 /m2 and both detached properties fell within the LETI (2020) target of 500 kg CO2 /m2 . However, all three properties would fail to meet the RIBA or 2030 LETI target of 300 kg CO2 /m2 . This suggests that improvements are necessary to achieve future targets. The results show that financial capabilities and operational energy prioritisation act as the main enabler and barrier for reducing embodied energy. Local contractors/suppliers, minimising material use or intensity, and modular construction were highlighted as the key reduction techniques that can be used to help achieve future targets concerning embodied carbon in residential developments. The study contributes significantly to understanding the current state of embodied energy use in affordable housing and provides new insights on how to deal with embodied energy if we are to meet future energy targets.
Keywords: affordable housing; carbon emission; case study; embodied carbon; embodied energy; sustainable construction; United Kingdom; zero carbon